2018
DOI: 10.1111/sode.12344
|View full text |Cite
|
Sign up to set email alerts
|

Parenting and children’s prosocial and problem behaviors in middle childhood: The role of Turkish mothers’ emotion socialization practices

Abstract: Mechanisms by which the relations between different parenting behaviors and children’s prosocial and problem behaviors occur are the focus of the current study. Supportive and nonsupportive emotion socialization practices of mothers were considered as potential mediators. Further, the moderator role of gender was explored. Participants were 228 mothers of 6‐ to 11‐year‐old children living in Ankara, Turkey. Scales assessing parenting behaviors (specifically, positive parenting and inconsistent discipline), mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…The results of this study show that at such times, when parents provide appropriate adult support and provide answers that help children understand and express their emotions, this has a preventive effect on the child's aggressive behavior. Many studies show that supportive emotional socialization behavior has a positive effect on the positive social behavior of children (Acar‐Bayraktar et al, 2018; Baker et al, 2011; Jones et al, 2002; Meyer et al, 2014); on the other hand, unsupportive emotional socialization behaviors lead to emotional disorder and failure to recognize emotions and, as a result, causes children to exhibit behavioral problems (Duncombe et al, 2012; Rogers et al, 2016). Other research has found that family processes, such as the emotion socialization of parents, maternal sensitivity and warmth, parental rejection, and positive or negative interactions between mother and child, shape the development of emotional regulation in both children and adolescents and that emotional regulation skills predict healthy functionality, social competence, depressive symptoms, and aggressive behaviors (Chang et al, 2003; Eisenberg, Losoya, et al, 2001; Morris et al, 2007; Olson et al, 2011; Yap et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study show that at such times, when parents provide appropriate adult support and provide answers that help children understand and express their emotions, this has a preventive effect on the child's aggressive behavior. Many studies show that supportive emotional socialization behavior has a positive effect on the positive social behavior of children (Acar‐Bayraktar et al, 2018; Baker et al, 2011; Jones et al, 2002; Meyer et al, 2014); on the other hand, unsupportive emotional socialization behaviors lead to emotional disorder and failure to recognize emotions and, as a result, causes children to exhibit behavioral problems (Duncombe et al, 2012; Rogers et al, 2016). Other research has found that family processes, such as the emotion socialization of parents, maternal sensitivity and warmth, parental rejection, and positive or negative interactions between mother and child, shape the development of emotional regulation in both children and adolescents and that emotional regulation skills predict healthy functionality, social competence, depressive symptoms, and aggressive behaviors (Chang et al, 2003; Eisenberg, Losoya, et al, 2001; Morris et al, 2007; Olson et al, 2011; Yap et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…For example, parents express explicit gender stereotypes by restricting their child's preferred gaming and reinforce traditional gender behavior by using gender labels (Endendijk et al, 2014). Other studies have found that parents are more likely to use supportive parenting strategies for girls than boys (Acar-Bayraktar et al, 2019;Grazyna et al, 2009). When parents respond differentially to the same behaviors in boys and girls, children will understand the differences between boys and girls and know that certain behaviors are only suitable for specific genders (Endendijk et al, 2018).…”
Section: Dominance Of Family Environment Factorsmentioning
confidence: 99%
“…Positive parenting, which comprised of parental warmth and support ( Llorca et al, 2017 ), parental involvement ( Ogunboyede and Agokei, 2016 ), as well as supportive emotion socialization ( Acar-Bayraktar et al, 2019 ), promotes prosociality in children ( Llorca et al, 2017 ). In an experiment by Acar-Bayraktar et al (2019) , positive maternal reactions were found to be positively associated with prosocial behaviors in children.…”
Section: Introductionmentioning
confidence: 99%
“…Positive parenting, which comprised of parental warmth and support ( Llorca et al, 2017 ), parental involvement ( Ogunboyede and Agokei, 2016 ), as well as supportive emotion socialization ( Acar-Bayraktar et al, 2019 ), promotes prosociality in children ( Llorca et al, 2017 ). In an experiment by Acar-Bayraktar et al (2019) , positive maternal reactions were found to be positively associated with prosocial behaviors in children. This finding is in agreement with the literature, which showed that parental practices of empathic responding ( Eisenberg et al, 2010 ; Van der Graaff et al, 2018 ), providing sympathetic expression ( Eisenberg et al, 2010 ), and modeling good behaviors ( Schuhmacher et al, 2019 ), promote prosocial behaviors.…”
Section: Introductionmentioning
confidence: 99%